LEGAL FOUNDATIONS AND CHALLENGES OF YOUTH POLICY IN UZBEKISTAN (Web of Technology: Multidimensional Research Journal, 2025)
Each society views youth as a "future deposit" aimed at advancing the state. The increasing number of young people in global demographics, rapidly adapting to the modern era, has led to their balanced presence on the world stage, preserving ideological concerns, and progressive movements recognized through international forums. However, the acceptance of evidence also implies the division of spiritual voids among youth in recent years, under the influence of psychological pressures, creating challenges to personal development. Naturally, demographic changes contribute to fluctuations in youth numbers across continents, whether increasing significantly or declining, due to various reasons. In the published scientific article, the distinctive features of the country's historical policy aimed at fostering a Third Renaissance with the youth, connecting them to the values of global civilization, were comprehensively studied and analyzed. This was done to elucidate the true essence and significance of the state's policy that contributes to the extensive international engagement in Uzbekistan.